Krill Oil and Its Bioactive Components as a Potential Therapy for Inflammatory Bowel Disease: Insights from In Vivo and In Vitro Studies. - Liu, Yingying; Robinson, Ainsley M; Su, Xiao Qun; Nurgali, Kulmira (Biomolecules, 2024)
Krill oil is extracted from krill, a small crustacean in the Antarctic Ocean. It has received growing attention because of krill oil's unique properties and diverse health benefits. Recent experimental and clinical studies suggest that it has potential therapeutic benefits in preventing the development of a range of chronic conditions, including inflammatory bowel disease (IBD). Krill oil is enriched with long-chain n-3 polyunsaturated fatty acids, especially eicosapentaenoic and docosahexaenoic acids, and the potent antioxidant astaxanthin, contributing to its therapeutic properties. The possible underlying mechanisms of krill oil's health benefits include anti-inflammatory and antioxidant actions, maintaining intestinal barrier functions, and modulating gut microbiota. This review aims to provide an overview of the beneficial effects of krill oil and its bioactive components on intestinal inflammation and to discuss the findings on the molecular mechanisms associated with the role of krill oil in IBD prevention and treatment.